2018
DOI: 10.1111/jomf.12543
|View full text |Cite
|
Sign up to set email alerts
|

Motherhood Penalties in the U.S., 1986–2014

Abstract: Objective: This article aims to determine whether the wage penalty for motherhood changed in the United States between 1986 and 2014 and to assess the relative impact of education and experience on the penalty over time. Background: Mothers earn less than childless women. Although mothers' educational levels and labor market experience have increased over time, most studies do not analyze the motherhood penalty over time. Method: This article uses ordinary least squares and fixed effects regressions to estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…Using the NLSY to follow a cohort of women from 1968 to 2003, Kahn, Garcia‐Manglano, and Bianchi () found the penalty was largest when women were young. Examining changes in the motherhood penalty from 1980 to 2014, Glauber () found that the penalty was eliminated for high‐earning, but not low‐earning, women (see also Buchmann & McDaniel, ; but see Jee, Misra, & Murray‐Close, ).…”
Section: Paid Work and Familiesmentioning
confidence: 99%
“…Using the NLSY to follow a cohort of women from 1968 to 2003, Kahn, Garcia‐Manglano, and Bianchi () found the penalty was largest when women were young. Examining changes in the motherhood penalty from 1980 to 2014, Glauber () found that the penalty was eliminated for high‐earning, but not low‐earning, women (see also Buchmann & McDaniel, ; but see Jee, Misra, & Murray‐Close, ).…”
Section: Paid Work and Familiesmentioning
confidence: 99%
“…Parenthood exac er bates gen der inequal ity in the labor mar ket (England 2005). Whereas men's wages remain sta ble or increase when they become fathers (Killewald 2013;Lundberg and Rose 2002), women expe ri ence a sub stan tial moth er hood wage penalty (Avellar and Smock 2003;Jee et al 2019). Some of the moth er hood wage pen alty can be explained by dif fer ences in work expe ri ence, part-time hours, and occu pa tional changes (Budig and England 2001), but a large resid ual pen alty per sists in research adjusting for these fac tors and selec tion into moth er hood (Waldfogel 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these changes in women’s employment, shifts in the motherhood wage penalty and fatherhood wage premium also have the potential to contribute to increases in spouses’ economic homogamy, although evidence about change over time is relatively weak. Some studies showed that motherhood wage penalties—which capture effects of work interruptions, job changes, and discrimination—have declined over the past decades ( Glauber 2008 ; Pal and Waldfogel 2016 ), but others found no substantial change ( Jee et al 2019 ). Studies have also found little change in fatherhood wage bonuses ( Glauber 2018 ; Lundberg and Rose 2000 ).…”
Section: Introductionmentioning
confidence: 99%